Legal Construction of Interfaith Marriage in Indonesia: Legal Reasoning and Multireligious Ratio Legis - Erfaniah Zuhriah; Su'ud Fuadi; Imam Sukadi; Jamrud Qomaruz Zaman; Siti Aisyah binti Samudin (Contemporary Issues on Interfaith Law and Society, 2026)
Supreme Court Circular Letter No. 2 of 2023, which prohibits interfaith marriage in Indonesia, continues to generate constitutional and legal debate. Opposition is largely based on universal human rights arguments, while support emphasizes religious and moral values. This study examines the ratio legis of the prohibition within the framework of Indonesia’s Staatsfundamentalnorm. Using normative legal research with statutory, philosophical, and case-based approaches, the study finds that both doctrinal-deductive and non-doctrinal (pragmatic)-inductive reasoning support the interpretation that the prohibition aims to protect the right to religious observance and implement the first principle of Pancasila as a constitutional value. At the same time, the regulation reflects an ongoing tension between the protection of religious values and the recognition of universal human rights in Indonesia’s pluralistic legal system. The implementation of the prohibition is hindered by several legal lacunae, including regulatory disharmony, ambiguity regarding marriages conducted abroad, the use of legal circumvention strategies, and the persistence of unregistered (siri) marriages. To strengthen legal certainty and governance of diversity, this study proposes: (1) statutory regulation of interfaith marriage prohibitions that accommodates religious and cultural considerations; (2) harmonization of related regulations; (3) application of the nationality principle; (4) marriage annulment based on apostasy; and (5) prohibition of siri marriages accompanied by punitive sanctions. These measures are intended to enhance legal certainty, protect rights, and improve the management of diversity within Indonesia’s multicultural legal system through stronger institutions and greater public legal awareness.